148k views
3 votes
F(1)=1 and f(n)=2f(n-1)f(n)=2f(n−1) then find the value of f(6)f(6).

User Eugene B
by
5.4k points

1 Answer

4 votes

Answer:

Correct option is

C

2

n

−1

Given that f(n+1)=2f(n)+1,n≥1.

Therefore, f(2)=2f(1)+1

Since f(1)=1, we have

f(2)=2f(1)+1=2(1)+1=3=2

2

−1.

Similarly f(3)=2f(2)+1=2(3)+1=7=2

3

−1

and so on....

In general, f(n)=2

n

−1

Was this answer helpful?Correct option is

C

2

n

−1

Given that f(n+1)=2f(n)+1,n≥1.

Therefore, f(2)=2f(1)+1

Since f(1)=1, we have

f(2)=2f(1)+1=2(1)+1=3=2

2

−1.

Similarly f(3)=2f(2)+1=2(3)+1=7=2

3

−1

and so on....

In general, f(n)=2

n

−1

Was this answer helpful?

Explanation:

User Fred Sauer
by
5.2k points